“Practice believing that the world can change radically”: Interview with Malka Older - Schwarz, Anke (Critical Reviews on Latin American Research - CROLAR, 2021)
For the Latin American Futures edition of CROLAR, Anke Schwarz had a written conversation with Malka Older, author and Faculty Associate at Arizona State University School for the Future of Innovation in Society, on speculative fiction, contemporary dystopias, and the future of borders and nation states. Older’s cyberpunk Centenal Cycle trilogy is a finalist for the Hugo Award for Best Series. Her latest publication is the 2019 short story collection …And Other Disasters from Mason Jar Press. The interview was conducted in August/September 2020.